APPLICATION OF EDUCATIONAL DIALOGUE TRAINING EXERCISES IN THE SCHOOL COURSE OF ECONOMIC AND SOCIAL GEOGRAPHIES OF UKRAINE - Tkachenko, O.L. (Pedagogy of Higher and Secondary Education, 2003)
O.L. Tkachenko. Postgraduate of the Chair o f Pedagogical Creativity, Sumy State Pedagogical University. The use of exercises o f educational dialogue in the school course of , Economic and social geography o f Ukraine”. For the purpose of providing with conditions of harmonious development of a pupil s personality in educational establishments of general education we have developed a set of exercises of educational dialogue. The use of the exercises, which are adopted to the course of , Economic and Social Geography o f Ukraine (9th form)”, is analyzed in the theses. Examples are given.